Assessing the inner setting among Massachusetts community health centers: opportunities for multilevel investigation and expansion of influences on health equity - Rebekka M. Lee; James G. Daly; Daniel A. Gundersen; Ruth I. Lederman; Susan Dargon-Hart; Jonathan P. Winickoff; Karen M. Emmons; the ISCCCE Partnership (Implementation Science Communications)
Abstract Background Implementation science increasingly aims to improve health outcomes in delivery of evidence-based interventions. It is important to understand the inner setting of organizations where interventions are put into place, as setting characteristics can have significant impact on implementation outcomes. Community health centers are increasingly engaged in efforts to improve use of evidence-based cancer control interventions. Taking a comprehensive, partnered approach to measuring the inner setting among a network of community health centers engaged in implementation research ensures assessment of the variability among sites. Methods We conducted a cross-sectional survey among staff (n = 63) purposively sampled from 12 community health centers in Massachusetts engaged in research at the Implementation Science Center for Cancer Control Equity. The survey assessed inner setting constructs from the Consolidated Framework for Implementation Research, including learning climate, leadership engagement, available resources, and implementation demands/stress using validated measures (Likert scale range: 1 “strongly disagree” to 5 “strongly agree”). Additional equity-focused inner setting items included structural characteristics of the work infrastructure and language access services. Descriptive statistics examined differences by staff role and health center. Results Staff rated learning climate (mean = 3.98) and leadership engagement (mean = 3.67) positively, while available resources (mean = 2.78) had the lowest rating, particularly staffing resources. Clinical staff rated the inner context lowest compared to other roles. All centers reported supportive human resource benefits for caregiving and 92% provided tuition assistance, while fewer offered formal mentorship (50%) or affinity groups (33%). Community health centers reported written materials are routinely provided to patients in languages other than English and interpreter services were most common in Spanish, Vietnamese, and Portuguese. Conclusions This study provides an assessment of the inner setting within Massachusetts community health centers at the start of a new research collaboration. Periodic follow-up surveys will monitor changes over time. Data can be used in future analyses to explore how inner setting characteristics influence implementation outcomes and impact equitable translation of evidence-based interventions into practice.